PERFORMANCE OF THE STATE CIVIL APPARATUS IN PUBLIC SERVICES IN NATIONAL UNITY AND REGIONAL POLITICAL AGENCIES OF NORTH SULAWESI PROVINCE - Strawinsky C.J Pantow; Rossy Lambelanova (Sean Institute, 2023)
ASN in carrying out tasks from the planning process to implementation has a major impact on community satisfaction, bureaucratic efficiency and on state development. However, the challenges faced by ASN in meeting community expectations are not easy. ASN must face various issues such as complex bureaucracy, policy changes, and demands to improve service quality. In the increasingly developing digital and e-Government era, public services have experienced significant changes. The application of information and communication technology is a powerful tool in creating efficiency, transparency and accessibility in public services. ASN is expected to not only follow technological developments, but also adapt quickly and proactively utilize technology to improve performance in public services. This research aims to describe and determine the performance of State Civil Apparatus employees in implementing Public Services at the National Unity and Regional Political Agency of North Sulawesi Province. The method used is qualitative descriptive. Data collection was carried out through library research, unstructured interviews, non-participatory observation, and accidental sampling. The data sources used are primary and secondary. In this research, it was concluded that the performance of State Civil Apparatus employees at the National Unity and Regional Political Agency of North Sulawesi Province in Public Services can be said to be good overall and is in the process of improving even better. However, the apparatus must improve and further improve its performance in services. public.